Analysis of injuries and causes of death in fatal farm-related incidents in Lower Silesia, Poland - Marta Rorat; Agata Thannhauser; Tomasz Jurek (Annals of Agricultural and Environmental Medicine, 2015)
Introduction Workers in the agriculture sector are among the groups at the highest risk of fatal occupational injuries. The aim of study is to show the most common causes of farm-related deaths in Poland, with the circumstances, injuries sustained and mechanisms of death.